Faktor-faktor yang mempengaruhi minat berwirausaha pada mahasiswa fakultas ekonomi universitas tarumanagara - Ayuningtias, Hazirah Amalia; Ekawati, Sanny (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this study was to determine whether there is a minimum of one variable influence of family environment, campus environment, personality, and entrepreneurship motivation towards entrepreneurship interest students of the Faculty of Economics, University Tarumanagara. This research was conducted using judgmental sampling method. Researchers distributed questionnaires to 310 respondents. From the research we concluded that the variables that most influence the interest in entrepreneurship students of the Faculty of Economics, University Taruamanagara is entrepreneurship motivation. The influence of the variable in sequence is personality, family environment and the campus environment. The results also showed that all variables have a positive and significant impact on the interest in entrepreneurship students of the Faculty of Economics, University Tarumanagara.